The effect of an educational program with a learning style under practice conditions on the learning outcomes of some offensive basketball skills - Shihab Ahmed, Mohammed; Khalid Jasim, Mayyadh (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research lies in applying a new learning method based on the use of skillful educational exercises under conditions similar to the conditions of the match in terms of the level of performance intensity to develop the accuracy of the performance of some types of correction of the research sample and reach them to an ideal level. As for the research problem, it lies in not taking into account the degree of physical and nervous excitement of learners when competition during matches during preparing the exercises used to learn basketball scoring skills. The current research also aimed to prepare an educational program using the method of learning under competition conditions through special exercises for some types of correction in the basket, as well as identifying the effect of the educational program on developing some correction skills in the basket. The researchers used the experimental approach, and the researchers identified the research community from the players of the specialized school basketball and ages (14-16). The number of 25 students who were chosen intentionally as they were divided randomly (by clouds) in two groups: the experimental group and 10 players and the control group and the number of 10 and excluded five players for not meeting deadlines Training units and tribal tests were conducted and then the educational program was implemented by 12 educational units and then conducting post-test. After applying the appropriate statistical means, the results showed the superiority of the experimental group members over the control group, and this indicates the advantage of the learning style under competition conditions over the method followed by the coach.